Project Zanzibar: A Portable and Flexible Tangible Interaction Platform - Villar, Nicolas; Cletheroe, Daniel; Saul, Greg; Holz, Christian; Salandin, Oscar; Regan, Tim; Sra, Misha; Yeo, Hui-Shyong; Field, William; Zhang, Haiyan (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
We present Project Zanzibar, a flexible mat that locates, uniquely identifies, and communicates with tangible objects placed on its surface, as well as senses a user's touch and hover gestures. We describe the underlying technical contributions: efficient and localised Near Field Communication (NFC) over a large surface area; object tracking combining NFC signal strength and capacitive footprint detection, and manufacturing techniques for a rollable device form-factor that enables portability, while providing a sizable interaction area when unrolled. In addition, we detail design patterns for tangibles of varying complexity and interactive capabilities, including the ability to sense orientation on the mat, harvest power, provide additional input and output, stack, or extend sensing outside the bounds of the mat. Capabilities and interaction modalities are illustrated with self-generated applications. Finally, we report on the experience of professional game developers building novel physical/digital experiences using the platform.
Best paper award